Collaborative Deprescribing in Borderline Personality Disorder: A Narrative Review. Issue 2 (March 2019) - Fineberg, Sarah K.; Gupta, Swapnil; Leavitt, Jacob
Abstract : Learning objectives: After participating in this activity, learners should be better able to: Assess medication management in patients with borderline personality disorder (BPD) Evaluate the role of deprescribing as an active intervention in patients with BPD treated with polypharmacy Abstract: Psychopharmacology in borderline personality disorder (BPD) is complicated by comorbid disorders, substance use, sensitivity to side effects, risk of self-harm through medication misuse, and intense but transient symptoms. Patients' relationships with medications may range from tenuous to highly enmeshed, and may profoundly influence the response to treatment. For these reasons, awareness of current evidence and flexible approaches are particularly relevant to prescribing in BPD. In this narrative review, we illustrate the current status of medication management in BPD by focusing on polypharmacy. We use a single vignette to explore the limitations of prescribing multiple medications and the factors contributing to polypharmacy. With the same vignette, and using the framework of deprescribing, we describe how medication regimens can be reduced to a necessary minimum. Deprescribing, originally developed in geriatric medicine, is an active intervention that involves a risk-benefit analysis for each medication, keeping in mind the patient's medical and psychiatric status and his or her preferences and values. Deprescribing lends itself well to use in psychiatry and especially in BPD because of its emphasis on the patient's preferences and on repeated conversations to revisit and update decisions. In addition to elaborating on the deprescribing framework, we provide recommendations for conducting these critical discussions about medications in BPD, with particular attention to the patient's relationship to the medication. Finally, we summarize our recommendations and strategies for implementing flexible and responsive medication management for patients with BPD. We suggest areas of future research, including testing the efficacy of targeted intermittent medication treatments.